New chemicals as possible alternatives to methyl bromide in the area of Valencia: Preliminary results - Cebolla, Vicent; Bartual, Rafael; Bustos, Julia; Giner, Alfonso (2017)
Research efforts must be directed towards new chemical alternatives before methyl bromide (MB) is phased out in 2005, thereafter its use will be restricted or prohibited. The main objective of this study is to investigate the efficacy of new combinations of known chemicals which were not used for pre-planting fumigation for strawberry production in the past. Four treatments were included in the experiment: Non-treated control (1); fumigation with MB at the standard rate of 60g/ m(2) (2); Telone II (1,3.Dicholopropene) at the dosage of 18 g/ m(2) followed by Metham-Na application at the rate of 108g/ m(2) (3); and Telone C35 (1,3.Dicholopropene with 35% of Chloropicrine) at the dosage of 28g/m(2). Parameters under investigation were: effect on disease inoculum buried at 10 and 30cm deep, plant vigour, weed control, yield and fruit size. Data were gathered from the 1998-1999 crops. Telone C35 and Telone II + Metham-Na treatments reduced the presence of fungi in soil. The former is more effective in the upper layers while the latter is better in the deeper ones. All treatments gave a significant increase in plant vigour compared with the control. The incidence of weeds was significantly higher in the treatments control plots compared with the rest of the treatments. Standard MB and Telone C35 treatments were more effective in this respect. In all treatments, marketable yield and fruit size were significantly larger than in the control. Marketable yield and fruit size in the standard MB and Telone C35 treatments were not significantly different. MB application gave a significantly larger yield and fruit size compared with Telone II+ Metham-Na. Generally speaking, Telone C35 could be considered as an alternative to MB in strawberry crops in the study area. This research must be continued to examine its long-term effects, including the possibility of occurrence of harmful side effects.